UV-assisted, template-free electrodeposition of germanium nanowire cluster arrays from an ionic liquid for anodes in lithium-ion batteries. (17th November 2017) - Chi, Caixia; Hao, Jian; Liu, Xusong; Ma, Xiaoxuan; Yang, Yu; Liu, Xiaoxu; Endres, Frank; Zhao, Jiupeng; Li, Yao
Abstract : The structure of Ge nanowire cluster arrays is beneficial for capacity retention of the electrode. Abstract : Germanium has emerged as a promising Li ion battery anode material due to its high theoretical capacity. The in situ growth of Ge nanowires on current collectors (binder-free electrodes) has attracted much attention owing to their good electrical contact, excellent strain accommodation ability, promising material durability and short Li ion diffusion distance. Herein, we report a facile and efficient technique to synthesize Ge nanowire cluster arrays (Ge NWCAs) on nickel foam through an ultraviolet light (UV) assisted, template-free electrodeposition process from 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([Emim]Tf2 N). As a binder-free anode material, a Ge NWCA electrode exhibits a specific capacity of 1612 mA h g −1 and retains 740 mA h g −1 up to 200 cycles at a current rate of 0.2C. The Ge NWCA electrode affords excellent rate capacity at 0.1C–2C and retains specific capacity as high as 959 mA h g −1 at 2C. Furthermore, the specific capacity well recovers to 998 mA h g −1 when the rate is reduced from 2C to 0.1C. UV assisted ionic liquid electrodeposition might open up a new avenue for the synthesis of semiconductor nanostructures.